Ethics concern in implementing health professional events - Jian, Le (Australasian Epidemiological Association, 2011)
On 21 September, the Australasian Epidemiological Association (AEA) Annual Conference 2011 - Combining Tradition and Innovation - was successfully closed on the banks of the beautiful Swan River in Perth, Australia. The annual AEA meeting provides a professional platform for policy makers, researchers, lecturers, and university students to present and share research activities relating to current and future epidemiological, biostatistical, and public health issues. As a member of the Perth Organising Committee, I was involved in approaching a number of organisations for sponsorship of this national event. While it is common sense that obtaining sufficient funding is one of the key elements of organising a successful conference, some members raised concerns that, as a professional association, it is inappropriate to accept sponsorship from commercial companies. Obviously, whether or not to accept commercial sponsorship is not a question that has a simple yes or no answer.